POLA BIMBINGAN BELAJAR ORANG TUA DI MASA PANDEMI COVID-19 - Nia Unfa; Adi Tri Nugroho (Academica: Journal of Multidisciplinary Studies, 2020)
This research is a study of the role of parental learning assistance in children during the Covid-19 pandemic. This study aims to describe several patterns of learning assistance applied by parents. This research method uses a qualitative approach. We collect data through questionnaires. This research is important because it is in order to reveal whether or not the parenting style applied by parents during the learning process from home.Keywords:Â role; parenting on study; pandemic